1997
DOI: 10.1002/(sici)1097-0185(199707)248:3<346::aid-ar7>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of the effects of long‐term denervation on the extensor digitorum longus muscle of the rat

Abstract: Background: In order to understand the cellular basis underlying the progressively poorer restorative capacity of long-term denervated muscle, we determined the effects of long-term denervation on the muscle fibers and satellite cell population of the rat extensor digitorum longus (EDL) muscle.Methods: In 36 male rats, the right hind legs were denervated, and EDL muscles were removed 2, 4, 7, 12, and 18 months later. Muscles were either fixed for electron microscopic analysis or were dissociated into individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
4
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 0 publications
10
95
4
4
Order By: Relevance
“…A recent electromicroscopic study revealed that the number of satellite cells rose 2 months after denervation, and subsequently declined with time [24]. In the present study, activated or proliferating satellite cells were detected following denervation with immunohistochemistry for embryonic MHC, MyoD and BrdU, although the activation and proliferation of satellite cells were much less prominent than those during muscle regeneration after necrosis.…”
Section: Activation Of Satellite Cells Following Denervationcontrasting
confidence: 54%
“…A recent electromicroscopic study revealed that the number of satellite cells rose 2 months after denervation, and subsequently declined with time [24]. In the present study, activated or proliferating satellite cells were detected following denervation with immunohistochemistry for embryonic MHC, MyoD and BrdU, although the activation and proliferation of satellite cells were much less prominent than those during muscle regeneration after necrosis.…”
Section: Activation Of Satellite Cells Following Denervationcontrasting
confidence: 54%
“…The value obtained also exceeded that of muscles from normal (innervated and gonad-intact) as well as denervated and gonad-intact rats (Nnodim, 1999). This level of nuclear enrichment in the Venable (1966) and Viguie et al, (1997). Value given as mean Ϯ standard error of three muscles.…”
Section: Discussionmentioning
confidence: 70%
“…Table 3 also shows the derivation of whole-muscle satellite cell content from total nuclear and satellite cell frequency data, assuming a stable myofiber population (Venable, 1966;Viguie et al, 1997). The satellite cell number computed for the muscle of hormone-replaced rats (Group B) was approximately an order of magnitude greater than that of the castrated rats in Group A (408.4 ϫ 10 3 vs. 38.08 ϫ 10 3 ).…”
Section: Satellite Cell Countmentioning
confidence: 99%
“…The exact mechanisms regulating the positioning of myonuclei in muscle fibres remain unknown; however, there are several candidates: microtubuli, the intermediate filament desmin, as well as blood vessels have all been shown to be involved in the localization and ⁄ or anchoring of nuclei in muscle fibres (Bruusgaard et al, 2006;Ralston et al, 2006). Aggregation of myonuclei has been reported in response to long-term denervation (Viguie et al, 1997) and the ongoing denervation-reinnervation process in aging skeletal muscle (Larsson & Ansved, 1995) may accordingly play an important role for the aggregation of myonuclei observed in the old men and women in this study. However, a significantly increased variability in nearest distances was only observed in muscle fibres expressing the type I MyHC isoform and the aging-related denervation process is not restricted to slow-twitch motor units according to experimental studies (Larsson & Ansved, 1995).…”
Section: Phenotypical Observationsmentioning
confidence: 99%